Electrical properties of individual and small ensembles of InAs/InP nanostructures - Vicaro, K. O.; Gutiérrez, H. R.; Bortoleto, J. R R [UNESP]; Nieto, L.; Von Zuben, A. A G; Seabra, A. C.; Schulz, P. A.; Cotta, M. A. (Wiley, 2006)
We investigate electrical properties of InAs/InP semiconductor nanostructures by conductive atomic force microscopy (C-AFM) and current measurements at low temperatures in processed devices. Different conductances and threshold voltages for current onset were observed for each type of nanostructure. In particular, the extremity of the wire could be compared to a dot with similar dimensions. The processed devices were used in order to access the in-plane conductance of an assembly of a reduced number of nanostructures. Here, fluctuations on I-V curves at low temperatures (<40 K) were observed. At these low temperatures and for a suitable range of applied voltages, random telegraph noise (RTN) in the current was observed for devices with dots. These fluctuations can be associated to electrons trapped in dots, as suggested by numerical simulations. A crossover from a semiconductor-like to a metallic transport behavior is also observed for similar parameters. © 2006 WILEY-VCH Verlag GmbH & Co. KGaA.
Keywords: InAs/InP nanostructures; InAs/InP semiconductor nanostructures; Random telegraph noise (RTN); Atomic force microscopy; Electric conductance; Electric potential; Electric properties; Electron transitions; Semiconducting indium; Thermal effects; Nanostructured materials